Microbial Synthesis of Heme b: Biosynthetic Pathways, Current Strategies, Detection, and Future Prospects - Qiuyu Yang; Juntao Zhao; Yangyang Zheng; Tao Chen; Zhiwen Wang (Molecules, 2023)
Heme b, which is characterized by a ferrous ion and a porphyrin macrocycle, acts as a prosthetic group for many enzymes and contributes to various physiological processes. Consequently, it has wide applications in medicine, food, chemical production, and other burgeoning fields. Due to the shortcomings of chemical syntheses and bio-extraction techniques, alternative biotechnological methods have drawn increasing attention. In this review, we provide the first systematic summary of the progress in the microbial synthesis of heme b. Three different pathways are described in detail, and the metabolic engineering strategies for the biosynthesis of heme b via the protoporphyrin-dependent and coproporphyrin-dependent pathways are highlighted. The UV spectrophotometric detection of heme b is gradually being replaced by newly developed detection methods, such as HPLC and biosensors, and for the first time, this review summarizes the methods used in recent years. Finally, we discuss the future prospects, with an emphasis on the potential strategies for improving the biosynthesis of heme b and understanding the regulatory mechanisms for building efficient microbial cell factories.